Case Report: Post-Partum SARS-CoV-2 Infection After the First French Uterus Transplantation - Ayoubi, Jean Marc; Carbonnel, Marie; Kvarnström, Niclas; Revaux, Aurelie; Poulain, Marine; Vanlieferinghen, Sarah; Coatantiec, Yves; Le Marchand, Mathilde; Tourne, Morgan; Pirtea, Paul; Snanoudj, Renaud; Le Guen, Morgan; et al. (Frontiers in surgery, 2022)
Absolute uterus factor infertility, whether congenital or acquired, renders the woman unable to carry a child. Although uterus transplantation (UTx) is being increasingly performed as a non-vital procedure to address this unfortunate condition, the immunosuppression required presents risks that are further compounded by pregnancy and during the puerperium period. These vulnerabilities require avoidance of SARS-CoV-2 infection in pregnant UTx recipients especially during the third trimester, as accumulating evidence reveals increased risks of morbidity and mortality. Here we describe a successful UTx case with delivery of a healthy child, but in which both mother and neonate developed asymptomatic SARS-CoV-2 infection seven days after RNA vaccination, on day 35 post-partum. Although the patient was successfully treated with a combination therapy comprised of two monoclonal antibodies, this case highlights the challenges associated with performing UTx in the era of Covid-19. More broadly, the risks of performing non-vital organ transplantation during a pandemic should be discussed among team members and prospective patients, weighing the risks against the benefits in improving the quality of life, which were considerable for our patient who achieved motherhood with the birth of a healthy child.